Literature Review: Factors Associated with the Incidence of Chronic Energy Deficiency in Pregnant Women - Rahmawati Rahmawati; Adi Nugroho; Nia Kania (GLOBAL HEALTH SCIENCE GROUP, 2026)
Chronic Energy Deficiency in pregnant women is a serious health problem because it increases the risk of complications during pregnancy, childbirth, and fetal growth. Various studies have shown that the prevalence of chronic energy deficiency remains high and is influenced by multidimensional factors such as nutritional status, socioeconomic status, knowledge, and access to health services. The purpose of this study was to conduct a literature review to identify factors of chronic energy deficiency to strengthen evidence-based prevention strategies, specifically dietary patterns, maternal knowledge, and husband or family support. The study used a literature review by searching articles in PubMed, ScienceDirect, and Google Scholar. The inclusion criteria were articles published between 2021 and 2025, cross-sectional design, full papers, and discussing variables related to chronic energy deficiency in pregnant women. The MeSH (Medical Subject Heading)-based keywords were